Μεταξύ Αττίλα και Βαϊανού. Το Βυζάντιο και οι νομαδικοί λαοί από το 453 έως το 558 - ΚΑΡΔΑΡΑΣ Γεώργιος (Byzantina Symmeikta, 2014)
<!–[if gte mso 9]> Normal.dotm 0 0 1 152 870 獫票楧栮捯洀鉭曮㞱Û뜰⠲쎔딁烊皭〼፥ᙼ䕸忤઱ 7 1 1068 12.0 <![endif]–><!–[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> <!–StartFragment–> Between Attila and Bajan. Byzantium and the nomads from 453 to 558 The paper highlights the relations of Byzantium with the nomads in the period between the collapse of the Hunnic hegemony in Central Europe and the coming of the Avars to the northern frontiers of the Empire. Taking into account the written testimonies, as well as the archaeological finds, the geographical area of the nomadic settlements, the conflicts and treaties with Byzantium, the role of the nomads in the Byzantine-Persian relations, the nomad mercenaries in the Byzantine army and certain Byzantine finds, as jewellery, swords, pendant capsule or other decorative motifs are considered. These relations are distinguished in two periods, before and after 491. During the first one, the Empire was able to control the activity of the nomads offering them settlement permit on Byzantine soil, while for the second is noted, beside the strong conflicts, the cultural influence of Byzantium through Christianity and, on the other hand, the nomadic influences on the Byzantine army. <!–EndFragment–>